2021
DOI: 10.21203/rs.3.rs-444579/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing a Practitioner-Friendly Behavior Model in Pakistan, India, and Nigeria

Abstract: Background: There is increasing interest in using social and behavior change (SBC) for Health Systems Strengthening (HSS) in low-and-middle income countries (LMICs) but few good examples of how behavioral insights could inform the design, implementation, and evaluation of HSS interventions. Practitioners would benefit from a practical behavior model that may be applied across behaviors, in multiple social contexts. We test the Fogg Behavior Model (FBM), which has this potential, in 3 different social and econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…We also found that HCWs with high motivation AND high ability had a nearly 4-times higher odds ratio of being fully vaccinated compared with HCWs with low motivation AND high ability (aOR = 3.48, p < 0.05). Consistent with previous studies [13,17], there was no statistically significant difference between the effect of high motivation AND low ability and the effect of low motivation AND high ability on being fully vaccinated. As mentioned, previous studies have found three levels of effects: (1) high motivation AND high ability; (2) high motivation AND low ability OR low motivation AND high ability; (3) low motivation AND low ability.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We also found that HCWs with high motivation AND high ability had a nearly 4-times higher odds ratio of being fully vaccinated compared with HCWs with low motivation AND high ability (aOR = 3.48, p < 0.05). Consistent with previous studies [13,17], there was no statistically significant difference between the effect of high motivation AND low ability and the effect of low motivation AND high ability on being fully vaccinated. As mentioned, previous studies have found three levels of effects: (1) high motivation AND high ability; (2) high motivation AND low ability OR low motivation AND high ability; (3) low motivation AND low ability.…”
Section: Resultssupporting
confidence: 90%
“…The magnitude of the effects of motivation and ability on vaccination uptake is consistent with findings observed in studies examining the adoption of other preventive health behaviors [13,14,17] and suggests that the FBM provides a robust framework for studying vaccine uptake among HCWs in an LMIC. The FBM provides a practitionerfriendly framework for measuring changes in the drivers of behavior using a limited number of variables.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…?") [30], but we have argued that those results do not provide sufficient nuance to inform the design of activities to address low motivation. Instead, as described above, this project developed and applied scale items to measure each of the six FBM motivation factors.…”
Section: Discussionmentioning
confidence: 86%